Implementing Science Creativity in Junior High School Students Using A Pirporsal Learning Model On Energy Resources - Lela Nurika; Kiki Septaria; Sri Setyaningsih (INKUIRI: Jurnal Pendidikan IPA, 2024)
It is vital to foster scientific creativity in Indonesian students as a result of a combination of project-based learning, simulations, and group discussions for students who wish to find innovative solutions to challenges. The purpose of this study is to determine if the proposal learning model can improve students' scientific creative skills in the field of electrical energy. This pre-experimental study used a one-group pretest-posttest design and was conducted at state junior high schools with a sample of 60 students from a student population of 176. Data gathering methods include observation and tests, and data analysis methods include learning implementation, N test -Gain, and t-test with the assistance of SPSS version 27 software. The findings of this study show that the pirposal learning model is implemented with an average observation score in the favorable category, then there is a significant influence between the pirposal model on students' scientific creativity with a t test significance value of 0.000, and there was an increase in the ngain test in the high category.